The Influence of User Involvement and Personal Technical Skills on the Performance of Accounting Information Systems at PT Pindad - Wendi Yuliawan; Bobby Wiryawan Saputra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research explores the impact of user involvement and technical competence on the effectiveness of the Accounting Information System (AIS) at PT Pindad. As a member of the Defend ID holding, PT Pindad supports the strategic goals of Indonesia’s state-owned enterprises (BUMN) in enhancing the national defense sector through the integration and restructuring of information systems. In February 2024, the company launched a system revitalization initiative, implementing SAP powered by High-performance Analytic Appliance (HANA) across its subsidiaries. The primary objective of this study is to assess how user participation and individual technical capabilities influence the performance of the newly adopted AIS. The study applies an associative research method using a stratified sampling technique, with 40 respondents participating. Multiple linear regression analysis was employed to examine the relationship between the independent variables (user involvement and technical competence) and the dependent variable (AIS performance). The results show that user involvement significantly impacts AIS performance, accounting for 41.76%, while technical competence contributes 42.24%. Collectively, both variables explain 84% of the system’s performance, with the remaining 16% attributed to other factors not addressed in this study.